Sea Buckthorn Proanthocyanidins are the Protective Agent of Mitochondrial Function in Macrophages Under Oxidative Stress - Liu, Keshan; Li, Wenxia; Yuen, Michael; Yuen, Tina; Yuen, Hywel; Wang, Min; Peng, Qiang (Frontiers in Pharmacology, 2022)
Sea buckthorn proanthocyanidins (SBP) are the most important antioxidant components of sea buckthorn, which are widely used in functional foods and cosmetics. Studies have shown that SBP have significant protective effects on macrophages against oxidative stress induced by hydrogen peroxide (H2O2). However, the mechanism remains uncertain. In the present study, we explored the effects of SBP on mitochondrial function and the mechanism of their protective effects against oxidative stress in cells. Our results showed that SBP could increase mitochondrial membrane potential, inhibit mPTP opening, reduce mitochondrial swelling, and enhance mitochondrial synthesis and metabolism. Thus, they alleviated oxidative damage and protected the cells against mitochondrial function. Western blot analysis showed that SBP had a protective effect on RAW264.7 cells by activating the AMPK-PGC1α-Nrf2 pathway. These results showed that SBP alleviated mitochondrial damage and dysfunction caused by oxidative stress. This study revealed the mechanism of SBP in reducing oxidative damage and provided a theoretical basis for further research on natural bioactive compounds to exert antioxidant activity and prevent arteriosclerosis and other diseases.